Mengadaptasi Efektivitas Peralatan Keseluruhan untuk Mengevaluasi Kinerja Operasional di Klinik Rawat Jalan Mata - Timotius Dwi Kurnianto; Timotius Febry Christian Wahyu Sutrisno (Journal of Economics and Management Scienties, 2026)
Ophthalmology services are facing increasing operational pressures globally due to factors like aging populations and the rising prevalence of eye conditions such as cataracts and glaucoma. Operational inefficiencies, including long waiting times, clinic congestion, and process variability, negatively affect patient care quality and service capacity. To evaluate the operational performance of Mojoagung Eye Clinic using the Overall Equipment Effectiveness (OEE) framework, adapted for outpatient ophthalmology services, and identify the main operational bottleneck. A quantitative descriptive-evaluative study was conducted at Mojoagung Eye Clinic, Indonesia, over a six-month period (September 2025 to February 2026). OEE, comprising three core dimensions, availability, performance, and quality was applied to assess daily clinic operations. Data were collected from clinic records, direct observation, and structured managerial interviews. The clinic’s OEE improved from 40% in September 2025 to 71% in February 2026. Performance showed the greatest improvement (+32 percentage points), while availability remained stable, and quality remained consistently high (96-98%). Despite improvements, performance remained the weakest component, indicating it as the main operational bottleneck. Performance improvement is critical to enhancing operational effectiveness in the clinic. The clinic should focus on optimizing service speed through better patient flow management, real-time monitoring, and extended service hours to reduce bottlenecks and improve overall efficiency.